Styrene-free water-thinnable unsaturated polyester resins with hydrophilic sulfonate groups for coating applications. Part I. Syntheses by polycondensation - Jankowski, P.; Rokicki, G. (Polimery, 2022)
Styrene-free water-thinnable polyester resins containing hydrophilic sulfonate groups were prepared by polycondensation method (Table 1). Sulfonate monomer with ethyl ester groups (1) or sodium salt of diethyl sulfosuccinate (2) (Fig. 1, 2) were used as monomers to give resins hydrophilic properties. These monomers were incorporated to polyester chain during polycondensation with allyl crosslinking monomer and diols, dicarboxylic acids or their anhydrides, commonly used for the preparation of unsaturated polyester resins. Two-stage synthesis let avoid precipitation of sulfonate monomer in non-polar reaction environment. On the basis of obtained unsaturated polyester resins the aqueous emulsions were prepared (Table 2, Fig. 3) and then the coatings cured with UV radiation. After curing the coating showed hardness exceeding 200 (measured by Persoz pendulum) and usefulness for coatings of wood (Table 3, Fig. 4).